A meditation on boredom: re-appraising its value through introspective phenomenology. Issue 1 (2nd January 2017) - Lomas, Tim
ABSTRACT: Boredom is almost universally regarded as a dysphoric mental state, characterised by features such as disengagement and low arousal. However, in certain quarters (e.g., Zen Buddhism), boredom is seen as potentially having great value and even importance. The current study sought to explore boredom through a case study involving introspective phenomenology. The author created conditions in which he would experience boredom for an hour and recorded his experience in real-time using a variant of the Experiencing Sampling Method. The data were analysed using an adaptation of Interpretative Phenomenological Analysis. The results indicated that the state of boredom contained three main sources of value: altered perception of time, awakened curiosity about the environment, and exploration of self. Consequently, the article offers a re-appraisal of boredom, suggesting that rather than necessarily being a negative state, if engaged with, boredom has the potential to be a positive and rewarding experience.